OPTIMIZATION MODELS TO SUPPORT ADAPTIVE ECONOMIC AND ECOLOGICAL DECISIONS IN “DIGITAL OILFIELD” MANAGEMENT - TUTS, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proposes new methodological approaches to the management of the "digitalt field", which is a new concept of process management in the upstream system, which is used by foreign oil and gas companies to increase the efficiency and profitability of their activities. Taking into account the specifics of making adaptive economic and environmental decisions regarding greenhouse gas emissions, as well as taking into account modern approaches to the digitalization of business processes in the oil and gas production industry, and also taking into account the importance of solving global environmental problems associated with man-made environmental pollution, we have developed an architecture of an intellectual strategy to support management decision-making regarding the problem of minimizing losses from eliminating the negative consequences of greenhouse gas emissions. Taking into account the specifics of the activities and technological processes of oil and gas production enterprises and the risks associated with their activities, a structural and logical scheme for preparing and implementing multi-criteria decisions in complex situations related to greenhouse gas emissions into the atmosphere and a database operation scheme for the management decision-making support system have also been formed, which is a significant methodological support for the "digital oilfield" concept, which is being introduced by some oil and gas production enterprises in Ukraine, in particular DTEK "Naftogaz". All this will make it possible to effectively implement the "digital oilfield" concept in the activities of oil and gas production enterprises, to build an optimal system of control and forecasting and prevention of emergency situations that result in emissions of hydrocarbons and greenhouse gases into the environment. The practical application of the proposed models will allow oil and gas production enterprises to significantly reduce losses due to hydrocarbon emissions and thereby increase the profitability of operations and improve the environmental situation in the field region.